Low cycle fatigue capacity of shell-to-base connections in stainless steel thin-walled tanks. (15th October 2021) - Colombo, J.I.; Herrera, R.A.; Almazán, J.L.
Highlights: Fatigue life of shell-to-base connection in stainless steel tanks is investigated. Rotation amplitude vs number of cycles to failure is presented for tank connections. Fatigue life of a case study stainless steel tank was evaluated. Abstract: Strong ground motion during earthquakes can induce the uplift of part of the base of partially anchored or unanchored steel tanks for liquid storage. This partial uplift may induce large inelastic rotation demands at the shell-to-base connections and possible low-cycle fatigue failure. Current tank design guidelines limit the rotation at this connection to 0.2 rad. Nevertheless, recent studies have shown that this limit may be overly conservative for shell-to-base connections of tanks made of carbon steel and thicknesses of the base plate between 6 mm and 10 mm. To the best of the authors' knowledge, no investigation has been reported on the shell-to-base connection rotation capacity of stainless steel liquid storage tanks. Aside from the material differences, the shell-to-base connections on stainless steel tanks have typical thicknesses between 2 mm and 6 mm and the connection geometries differs from the ones used for carbon steel tanks. Therefore, in this paper, a numerical study is carried out in order to evaluate the rotation capacity of shell-to-base connections in stainless steel storage tanks. First, modelling methods and a low cycle fatigue criterion are validated using experimental data from carbon steel tank connection tests. Then, stainless steel connections with thickness of 2 mm, 4 mm and 6 mm are evaluated. Results from this study are presented as plots of rotation amplitude vs. number of cycles to failure (i.e., R-N curves). These results show that a stainless steel tank connection could reach about 180 cycles at 0.2 rad which may represent rotation capacities larger than those established by current design standards.